EXTH-62. THE DIELECTRIC PROPERTIES OF MALIGNANT GLIOMA TISSUE. (5th November 2018) - Proescholdt, Martin; Haj, Amer; Doenitz, Christian; Brawanski, Alexander; Bomzon, Zeev; Hershkovich, Hadas
Abstract: OBJECTIVE: Recently, tumor treating fields (TTFields) have been established as a new treatment for newly diagnosed glioblastoma (GBM). One of the most crucial parameters defining the treatment efficacy of TTFields is the electric field intensity. The electric properties of the normal intracranial compartments are well established, allowing the prediction of the electric field distribution. In contrast, there is no data available about the electric properties of tumor tissue, which leads to a lack of information regarding the electric field intensity within the tumor. In this study we will determine the dieclectric properties of malignant glioma by analyzing resected tissue following a fast acquisition protocol. METHODS: 20 patients with high grade glioma are currently being recruited. Tissue probes are acquired from the infiltration zone, vital tumor area, and perinecrotic compartment. The tissue was analyzed immediately after acquisition to avoid artifacts by temperature change, change of fluid composition as well as post resection ischemia. A cylindrical fragment is dissected from each tissue sample and is placed into a cylindrical cell with a known diameter. The impedance is recorded at frequencies 20Hz-1MHz using a software specifically developed for this study, which controls the LCR meter (Keysight Technologies, Santa Rosa, USA). The measured impedance is then translated into dielectric properties of the sample (conductivity and relative permittivity) based on the parallel plate model, the recorded complex impedance and the geometry of the samples. Each tissue probe will be fixed, H&E stained and histologically analyzed for tumor cell count and specific tissue features (infiltration into normal brain, vital tumor area, necrosis). RESULTS: The study has received a positive vote from the Ethical Board of the University Regensburg Medical Center. The first patients are being recruited, the actual results will be evaluated and presented during the meeting.